2003
DOI: 10.1108/08876040310461282
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation and performance in service firms: role of innovation

Abstract: There is wide acceptance of the precept that market orientation is associated with superior firm performance. However, empirical support for the proposition in prior literature is weak. This study examines the relationship between market orientation and performance with data from 201 international hotels and finds that market orientation is positively associated with both judgmental measures of performance ± service quality, customer satisfaction, and employee satisfaction, and objective measures of performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
416
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(448 citation statements)
references
References 28 publications
20
416
1
11
Order By: Relevance
“…Therefore, when opportunities are first glimpsed, sensing capability could not only help firms to understand which technologies should be explored, but also provide the necessary foundation for them to figure out which market segments should be targeted (Teece, Pisano, & Shuen, 1997 (Agarwal, Krishna Erramilli, & Dev, 2003). Based on the aforementioned positive relationship between innovation and performance, we propose the following hypotheses:…”
Section: Sensing Capabilitymentioning
confidence: 99%
“…Therefore, when opportunities are first glimpsed, sensing capability could not only help firms to understand which technologies should be explored, but also provide the necessary foundation for them to figure out which market segments should be targeted (Teece, Pisano, & Shuen, 1997 (Agarwal, Krishna Erramilli, & Dev, 2003). Based on the aforementioned positive relationship between innovation and performance, we propose the following hypotheses:…”
Section: Sensing Capabilitymentioning
confidence: 99%
“…On the other hand, there is a limited number of articles focusing on innovations in the hotel sector (Agarwal et al, 2003;Frehse, 2005, Ottenbacher and 3. innovation activity is higher in hotels operating in hotels chains (Or…la-Sintes et al, 2005). Moreover, Ottenbacher and Gnoth (2005) found that hotels operating in chains and independent hotels vary greatly in terms of the elements determining the success of new services;…”
Section: Innovation In Tourism -Literature Reviewmentioning
confidence: 99%
“…ability o customize dishes) and increase profits. Positive correlation between aforementioned marketing activities and business success was found by many authors (Agarwal et al, 2003;Sin et al, 2005;Leskiewicz Sandvik, Sandvik, 2003). Moreover, they should stay well informed about the trends within the industry by following relevant publications or through contact with faculties, educational centers and similar institutions and associations and facilitate the innovation process in that regard.…”
Section: Implications and Limitations Of The Studymentioning
confidence: 99%